The predictive utility of unmet need on time to contraceptive adoption: a panel study of non-contracepting Ugandan women - Dana Sarnak; Amy Tsui; Fredrick Makumbi; Simon P.S Kibira; Saifuddin Ahmed (Elsevier, 2020)
Objective: The predictive utility of the unmet contraceptive need indicator is not well known, despite being recognized as a key family planning indicator for showing the extant demand for birth control. This study assesses the dynamic influence of unmet need on time to contraceptive adoption, as compared with that of contraceptive intentions and their concordance. Study design: This observational study analyzed survey data, including a contraceptive calendar, reported by a panel of 747 non-contracepting, fecund and sexually active Ugandan women, first interviewed in a 2014 national survey and re-interviewed in 2018. We conducted descriptive, survival and multivariate Cox regression analysis of the influence of women's baseline measures of unmet need, self-reported intention to contracept and their concordance with time to adoption of modern contraception over 36 months. Results: The study found women classified as having unmet need were slower to adopt contraception than those without unmet need, after adjustment for background covariates (aHR=0.79, 95% CI=0.57-1.10). Women intending future contraceptive use were significantly faster to adopt (aHR=1.45, 95% CI=1.22-1.73) than those not intending. Women with no unmet need but intending to use had the highest rate of adoption compared to those with no need and no intention to use (aHR=2.78, 95% CI=1.48-5.25). Conclusions: The unmet need indicator underperforms in predicting future contraceptive adoption compared to contraceptive intentions, which merits further consideration as a complementary predictor of future use. Non-contracepting women with unmet need but no intention to use contraception in particular warrant programmatic attention. Implications: A non-contracepting woman wanting to limit or space her births is defined as having unmet need, but little is known if she subsequently adopts contraception. By contrasting a woman's unmet need with her expressed intention to use, we offer reasons to further consider self-reported contraceptive intentions as a better predictor of adoption and the underlying latent demand for volitional regulation of fertility.